Policy Implementation of Waste Management at Bintang Mangrove Waste Bank, Surabaya City - Jannah, Eka Maidhatul; Wibawani, Sri (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to describe and analyze the implementation of waste management policies at the Bintang Mangrove Waste Bank in Surabaya City, based on the Minister of Environment and Forestry Regulation No. 14 of 2021 and Surabaya Regional Regulation No. 1 of 2019. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The theoretical framework is based on the Policy Implementation theory by Randall B. Ripley and Grace A. Franklin (1986:232). The findings indicate that policy implementation was carried out through two main aspects: waste reduction and waste handling. Reduction efforts included recycling and reusing waste, which had both economic and environmental impacts. Waste handling involved sorting, collecting, processing, and delivering waste. The Bintang Mangrove Waste Bank also played a significant role in educating the community through the